Impact of Prior Knowledge about Autonomous Vehicles on the Public Attitude - Kareem Othman (Civil Engineering Journal, 2023)
It is anticipated that AVs will offer multiple benefits, such as an improvement in the level of mobility, increasing the level of comfort, and reducing the number of traffic accidents. However, the public attitude is the main determinant factor that will face the deployment of AVs and in turn affect their implications. Over the last few years, there was a debate on the impact of the level of knowledge about AVs on public attitudes. While some studies show that people with higher levels of knowledge about AVs are the most optimistic, some other studies show that the public attitude moves in the negative with an increase in the level of knowledge. Thus, this study focuses exclusively on quantifying and understanding the impact of the level of knowledge and the public attitude in the US. A questionnaire survey was designed and conducted between June and November, 2022. A total of 5778 complete responses were received from all over the US and the analysis was conducted to estimate the public attitude and level of knowledge by region. The results show that there is a negative shift in public attitude with the increase in the level of knowledge about AVs. In addition, the results show that 1% increase in the level of knowledge about AVs is associated with 0.65%, 0.68%, and 2466 (USD) $ decrease in the level of interest, trust, and willingness to pay for AV and 0.56% increase in the level of concern about traveling in AVs. Moreover, the results are discussed in light of both the diffusion of innovation theory and the Gartner Hype curve. Doi: 10.28991/CEJ-2023-09-04-017 Full Text: PDF